Peningkatan Kemampuan Kader Posyandu Ibnu Sina Gampong Barabung dalam Menentukan Status Gizi Balita Menggunakan Instrumentasi Digital - Yunidar, Yunidar; Melinda, Melinda; Hasan, Hafidh; Away, Yuwaldi (Nawadeepa: Jurnal Pengabdian Masyarakat, 2023)
The number of stunting children in the Aceh Besar region until the end of 2022 reached 1,211 cases, so that the Aceh Government and all stakeholders were very focused on reducing the number of stunting cases according to the target set by the Government of the Republic of Indonesia. To help determine the stunting case in Aceh Besar, an accurate digital measuring device is needed so that the prevention process is carried out on the right target. This community service activity is carried out continuously by applying the results of research measuring automatic nutritional status in children through high measurement and weight implemented at the Gampong Barabung Posyandu by training 12 Posyandu cadres in order to use the measuring instrument correctly. The method carried out is through practice and trials so that posyandu cadres that have been trained can determine the number of stunting cases in their area appropriately.